Effect of optical-reflection method of accommodative facility training on meridional acuity in astigmats with amblyopia - V. A. Kolomiyets; O. V. Kachan (Ukrainian Society of Ophthalmologists, 2021)
Background: The efficacy of accommodative facility training as a method of treatment for meridional amblyopia (MA) in astigmatic children with amblyopia was studied. MA manifests itself as selective alterations in visual acuity (VA), with substantial differences in the ability to resolve contours of different orientations, and may cause impairments in mechanisms of integrated processing of visual stimulus, development of cognitive abilities in children and visual performance. Purpose: To assess the effect of optical-reflection method of accommodative facility training on vernier acuity in meridians (MVA) in the treatment of astigmatic children with amblyopia. Material and Methods: Twenty seven children aged 5 to 12 years, with both refractive amblyopia and with-the-rule hyperopic astigmatism were included in the study, and underwent an examination. The spherical component of refraction ranged from +0.5D to +5.5D, and the cylindical component, from 0.5D to 4.5D. Best-corrected visual acuity (Sivtsev Chart) was assessed. Accommodative facility training was performed monocularly by image defocusing with lenses of a variable power. A +0.5-D sphere was placed just in front of the best correction for the study eye in order to blur this line. The +0.5-D sphere was replaced by a -0.5-D sphere after the optotypes became clearly visible. Thereafter, the training cycle was repeated using a ±0.75-D sphere and, subsequently, a ±1.0-D sphere. Lens power was gradually increased until it could be compensated by accommodation. The treatment course consisted of one training session a day for 10 days. Special computer software was used to determine corrected MVA. Linear objects were presented on the computer screen, and the smallest lateral displacement of one line from another that can be detected by the examinee will characterize the level of MVA. Results: A new algorithm was proposed for assessing the efficacy of treatment of MA in astigmats, with refractive asymmetries and meridional asymmetries in vernier acuity considered as vector quantities. It was demonstrated that a group of amblyops with the same type of astigmatism was not homogeneous. It was found possible to split such a group of patients into three clusters that differ in the type of variation in meridional acuity in the orthogonal meridians compared to refractive asymmetries. One cluster had equal vernier acuities in the vertical and horizontal meridians, the second had vernier acuity in the horizontal meridian better than in the vertical meridian, and the third had vernier acuity in the horizontal meridian worse than in the vertical meridian. MVA was greater in magnitude in one of the orthogonal meridians than in another in the dominant eyes in 37% of study patients, and in the fellow eyes in 50% of study patients. MVA values in the orthogonal meridians were similar in 56.6% of study patients. There was a 15.1-percent increase, from 56.6% to 71.1% in the number of eyes with a similar vernier acuity in the orthogonal meridians after treatment. A positive effect was achieved through elimination of meridional asymmetry in vernier acuity in a portion of patients from clusters that differ in the direction of meridional asymmetry in vernier acuity. In addition, the number of eyes in the category of patients with a visual acuity of 0.75-0.8 (as assessed with complex optotypes) increased by 11.35%. Conclusion: The efficacy of treatment for MA should be assessed in homogeneous clusters with similar direction of meridional asymmetry in visual acuity. Preliminary data on the efficacy of treatment of amblyopia by accommodative facility training allows considering this training as a method of treatment for meridional amblyopia. The method of determination of meridional acuity should be included in the standard examination of patients with amblyopia.